2000
DOI: 10.1103/physrevb.62.14268
|View full text |Cite
|
Sign up to set email alerts
|

Critical evolution of spin-reorientation transition in magneticCoxNi1x/Cu

Abstract: The ultrathin Co x Ni 1Ϫx /Cu(100) alloy films with low Co concentration xр10% was prepared for probing the effect of the d-band filling on the magnetic behavior. The perpendicular magnetization was observed only for films with xϽ10%. The spin-reorientation transition from the in-plane to perpendicular orientation was found to be extremely sensitive to the Co concentration. The critical thickness for the spin reorientation transition was changed drastically from 7.5 to 17.5 ML by varying x from 0 to 8 %. Since… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 27 publications
0
28
0
Order By: Relevance
“…It becomes crucial to confirm the structural invariance on the variation of the alloy composition. In the previous study, we found that the crystalline structure, lattice constant, as well as morphology of Co x Ni 1Àx /Cu(1 0 0) and Fe x Ni 1Àx /Cu(1 0 0) are invariant with alloy composition [10,11,9]. In addition, all these alloy films behave like the Ni/ Cu(1 0 0) film.…”
Section: Resultsmentioning
confidence: 91%
See 3 more Smart Citations
“…It becomes crucial to confirm the structural invariance on the variation of the alloy composition. In the previous study, we found that the crystalline structure, lattice constant, as well as morphology of Co x Ni 1Àx /Cu(1 0 0) and Fe x Ni 1Àx /Cu(1 0 0) are invariant with alloy composition [10,11,9]. In addition, all these alloy films behave like the Ni/ Cu(1 0 0) film.…”
Section: Resultsmentioning
confidence: 91%
“…No SRT was found for x > 6% with the coverage up to 20 ML. In comparison with Co x Ni 1Àx / Cu(1 0 0) [10] (open and solid triangles in Fig. 1), d c of the Fe x Ni 1Àx /Cu(1 0 0) alloy film is more sensitive to the content of Fe.…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…Similar to the system of 1 ML Ni/ 1 ML Co/Pt(1 1 1) film, the variations of relative Co and Ni signals may be due to the intermixing of Co and Ni [7]. In the MOKE studies of Co x Ni 1Àx / Cu(1 0 0) system, the MO responses were strongly dependent on the concentration of Co [8]. After annealing, the film was irreversible with y K of about 0.06 at RT.…”
Section: Methodsmentioning
confidence: 90%